Productivity and yield stability of crop sequences in Haryana and Punjab - KATYAL, V; GANGWAR, B; BHANDARI, A L (The Indian Journal of Agricultural Sciences, 2014)
The field trials conducted at Hisar from 1987-88 to 1992-93 and at Ludhiana form 1991-92 to 1996-97 involving 6-8 crop sequences revealed that pearlmillet [Pennisetum glaucum (L.) R.Br.emend. Stuntz]-Wheat (Triticum aestivum L. emend. Fiori & Paol.)-tomato (Lycopersicon esculentum Miller nom. cons.) and pearlmillet-potato (Solanum tuberosum L.)- sunflower (Helianthus annuus L.) were distinetly better yielding in terms of wheat-equivalent of 8 022 and 8 676 kg/ha and productivity of 26.3 to 26.7 kf/ha/day compared to existing pearlmillet-wheat sequences in Haryana. In Punjab rice (Oryza sativa L.)-Potato-groundnut (Arachis hypogaea L.) was identified to be distinetly productive in terms of wheat-equivalent (19 163 kg/ha) and productivity (53.7 kg/ha/day) compared with the existing rice-wheat sequence, yielding 10 016 kg/ha and with productivity of 37.2 kg/ha at Ludhiana. MoreoverinÂ  terms of yield stability the existing cropping systems were unstable at both the locations. Available N, P and K improved from initival values of 73, 17 and 287 to 126 , 27, 363 kg/ha, respectively, at Hisar and from 72.25 and 70 kg/ha to 116.5, 43.1 and 127.43 kg/ha respectively at Ludhiana. Thus soil fertility improved over years under intensive cropping at recommended levels of nutrients.